"Innere Abwertung" in Südeuropa: Erwartungen, Ergebnisse und Folgen - Heimberger, Philipp (Wirtschaft und Gesellschaft, 2014)
In dealing with the crisis in the Southern European countries Greece, Italy, Portugal and Spain, the Troika pushes for internal devaluation: Putting downward pressure on wages and prices in the South of the Eurozone is expected to cause improvements in price competitiveness and adjustments in current account balances via the export channel. As a consequence of demand-driven deflation tendencies, the Southern European countries are in danger of falling further into a vicious cycle of debt deflation. Over the last couple of years, the Troika has underestimated the negative effects of internal devaluation on economic growth and employment. Current developments in Southern Europe are broadly consistent with deflation experiences of European gold bloc countries during the 1930s. To a significant extent, drastic adjustments in current account balances between 2010 and 2013 are due to the slump in aggregate demand and the corresponding effects on imports.